2022
DOI: 10.47162/rjme.62.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride and glucose index: a useful tool for non-alcoholic liver disease assessed by liver biopsy in patients with metabolic syndrome?

Abstract: Introduction: Non-alcoholic fatty liver disease (NAFLD) is associated with metabolic impairments, being a component of metabolic syndrome. Considering the involvement of fat accumulation and insulin resistance in NAFLD, triglyceride and glucose (TyG) index was proposed as a marker of NAFLD progression. The "gold standard" for the evaluation of liver lesions characteristic for NAFLD remains the liver biopsy. The aim of this study was to establish the links between TyG index, assessing insulin resistance, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Elevated TyG index is an independent predictor of MAFLD and is positively correlated with the MAFLD fibrosis score and FIB-4 index, suggesting that a significant increase in the TyG index may indicate the development of liver fibrosis[ 31 ]. In 113 patients with histologically confirmed NAFLD, the TyG index levels were significantly higher in the F3 fibrosis stage than in the F0–F1 stage ( P < 0.0001)[ 32 ]. However, Guo et al [ 30 ] found that the AUC value of the TyG index for predicting NAFLD was 0.761, while its AUC value for predicting liver fibrosis was 0.589, indicating that the TyG index has a relatively low accuracy for predicting NAFLD-associated liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated TyG index is an independent predictor of MAFLD and is positively correlated with the MAFLD fibrosis score and FIB-4 index, suggesting that a significant increase in the TyG index may indicate the development of liver fibrosis[ 31 ]. In 113 patients with histologically confirmed NAFLD, the TyG index levels were significantly higher in the F3 fibrosis stage than in the F0–F1 stage ( P < 0.0001)[ 32 ]. However, Guo et al [ 30 ] found that the AUC value of the TyG index for predicting NAFLD was 0.761, while its AUC value for predicting liver fibrosis was 0.589, indicating that the TyG index has a relatively low accuracy for predicting NAFLD-associated liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Following a hepatic histopathological examination, we observed that the highest proportion of microscopic lesions was represented by associated chronic lesions, followed by hepatocellular necroinflammatory lesions like granulo-vacuolar dystrophy or lympho-monocytic periportal inflammatory infiltrate, and in a limited number, vascular lesions like microthrombosis. Hepatocellular dystrophy is itself nonspecific and is observed in both acute infectious hepatobiliary conditions and non-infectious hepatitis, and can also be seen in chronic liver conditions, for example, in hepatic dystrophies associated with metabolic syndromes [ 23 ]. Periportal inflammation can be triggered by a wide range of conditions, including some with necro-inflammatory activity, including viral hepatitis, autoimmune hepatitis, or drug-induced hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the diagnosis of NAFLD was made by ultrasonography, which is an operator-dependent test, and its sensitivity for the diagnosis of NAFLD may be lower in people with obesity. However, it is recently shown that the TyG index is associated with histopathological findings of NAFLD in liver biopsies [ 42 ].…”
Section: Discussionmentioning
confidence: 99%